Penerapan Nilai-Nilai Demokrasi Bung Hatta dalam Pendidikan Karakter di Sekolah Dasar: Strategi untuk Membangun Kemandirian dan Partisipasi Siswa - Nurul Fadhli; M.Nursi; Hendrizal; Devika Sri Yunda; Halimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of democratic values according to Bung Hatta in character education at SDN 003 Beringin Taluk, Kuantan Singingi Regency, Riau. This research uses a descriptive qualitative approach with classroom teachers and fifth and sixth-grade students as subjects. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed thematically. The results show that democratic values are applied through class deliberation, distribution of responsibilities, group collaboration, and active discussions, which foster student participation, independence, responsibility, tolerance, and respect for differences. Teacher strategies that integrate deliberation, collaboration, and autonomous decision-making are proven effective in shaping students’ democratic and participatory character. This study emphasizes that democratic education in elementary schools should be designed contextually, creatively, and sustainably, allowing Bung Hatta’s democratic values to be effectively internalized in students’ character